Sedative Effect of Midazolam Elixir Compare to Vial Through Oral Route in Uncooperative Pediatric Dental Patients - Masoud Fallahinejad Ghajari; Ghasem Ansari; Sarira Zomorrodian; Shahnaz Shayeghi (Islamic Dental Association of Iran, 2017)
Background and Aim: Midazolam is among routine agents used for inducing safe sedation. This study was designed to compare the sedative effect of oral administration of midazolam (Elixir vs Vial) in fearful children during dental treatment. Materials and Methods: A randomized double blind clinical trial was conducted in a cross over style on 20 young fearful aged 3-6 years with Frankl behavioral scale of 1. Children were randomly divided into two groups. Group I received 0.5 mg/kg Midazolam Vial and 1 mg/kg Hydroxyzine oral at their first visit and 0.5 mg/kg Midazolam Elixir and 1 mg/kg Hydroxyzine oral in their second visit. In group II, the medication order was reversed. Houpt scale was used to measure the sedation level in both groups. Vital signs of heart rate and SpO2 were recorded during the procedure. Paired t-test, Wilcoxson and McNamara were employed to statistically analyze and compare the collected data between two groups. Results: Based on the collected data, Houpt scale was seemingly improved more after taking elixir compare to the vial, however the difference was not statistically significant (P= 0.393). There was no significant difference between the success rate of the two methods (P= 0.625). All physiologic parameters were within the normal range with no significant difference between two groups and sessions. Conclusion: The level of success between the two groups for sedation was not statistically different and were almost the same. This may indicate a successful use of the vial for oral application in certain cases of compromised cooperation.